The coexistence of obesogenic behaviors among Brazilian adolescents and their associated factors - Thales Philipe Rodrigues da Silva; Fernanda Penido Matozinhos; Lúcia Helena Almeida Gratão; Luana Lara Rocha; Monique Louise Cassimiro Inácio; Cristiane de Freitas Oliveira; Tatiana Resende Prado Rangel de Oliveira; Larissa Loures Mendes (BMC, 2022)
Abstract Background The prevalence of obesity in adolescents has increased significantly in recent years. The growth of obesity is motivated by the association with modifiable behaviors, however, this behavioral are commonly evaluated individually, not considering the possibility of these factors coexisting in the individual. The purpose of this essay was to identify the coexistence of obesogenic behaviors among Brazilian adolescents and to assess the factors associated with the presence of these behaviors. Methods This a cross-sectional, national, school-based study with data from the Study of Cardiovascular Risks in Adolescents (ERICA), totaling a sample of 71,552 Brazilian adolescents. To identify the coexistence of obesogenic behaviors in adolescents, the Principal Component Analysis has been performed. To assess the association between factors that influence the coexistence of modifiable behaviors in the pattern of obesogenic behavior, logistic regression was used. The magnitude of the associations was estimated by the Odds Ratio (OR), with the respective 95% confidence intervals (95%CI). Results The component was characterized by a higher percentage of ultra-processed food intake, longer in front of screens, having a habit of snacking in front of the television, and not having the habit of eating breakfast. In the adjusted logistic model, it shows that female adolescents and who declare themselves black are more likely to belong to the third tertile of the pattern of obesogenic behavior. As for teenagers who sometimes or almost always or always have lunch or dinner with parents or guardians, who have longer hours of sleep and who live in economically disadvantaged regions have reduced chances of belonging to the third tertile of the pattern of obesogenic behavior. Conclusion The identification of obesogenic behavior patterns allows assertive interventions to eliminate or reduce these changeable behaviors, also aiming at the possibility of reducing obesity among adolescents.